Physical characterization of therapeutic proton delivery through common dental materials. Issue 5 (21st March 2022) - Hu, Yue‐Houng; Wan Chan Tseung, Hok Seum; Mundy, Daniel W.
Abstract: Purpose: Dental fixtures are commonplace in an aging, radiation treatment population. The current, local standard of practice in particle therapy is to employ treatment geometries to avoid delivery through implanted dental fixtures. The present study aims to observe the physical effect of delivering therapeutic proton beams through common dental fixture materials as prelude to an eventual goal of assessing the feasibility of using treatment geometries not specified for avoidance of oral implants. A sampling of common dental materials was selected based on prosthodontic consult and was evaluated in terms of relative stopping power and three‐dimensional (3D) dose perturbation. Methods: Amalgams, porcelain‐fused‐to‐metal (PFM) crowns consisting of zirconia and non‐noble base metals, and lithium disilicate implants were chosen for analysis. Theoretical stopping power ( S ) and mass stopping power ( S / ρ ) were calculated using the Stopping and Range of Ions in Matter (SRIM) application, basing stoichiometric compositions of each fixture on published materials data. S and S / ρ were calculated for a range of historically available compositions of amalgams from 1900 until the current era. The perturbance of S and S / ρ as a function of clinically relevant ranges of amalgam compositions for the modern era was analyzed. Water equivalent thickness (WET) and relative stopping power ( S rel ) of each material was measured for a clinical spot‐scanning proton beam with monoenergies of 159.9 and 228.8 MeV with a multi‐layer ionization chamber (MLIC). Subsequently, 3D dose perturbation was assessed by delivering proton beams through a custom phantom designed to simulate both en‐face and on‐edge treatment geometries through the selected materials. A treatment plan mimicking the experimental delivery was constructed in the institutional treatment planning system and calculated using TOPAS‐based Monte Carlo simulation (MCS). Experimental results were used to validate the MCS. Finally, treatment planning system (TPS) outputs were compared to MCS to determine the accuracy of the dose calculation model. Results: Historical compositions of amalgams ranged in S from 44.8 to 42.9 MeV/cm, with the greatest deviation being observed for the 1900–1959 era. Deviation as a function of amalgam composition from the modern era was most sensitive to proportion of Hg, accounting for deviations up to ‐4.2% at the greatest clinically relevant concentration. S / ρ was not found to vary greatly between each porcelain and metal alloy material for PFM type crowns. Relative stopping powers ranged between 1.3 and 5.4 for all studied materials, suggesting substantial changes in proton range with respect to water. Film measurements of pristine spots confirm dose perturbance and shortening of proton range, with an upstream shift of each Bragg peak being observed directly behind the installed fixture. At high energies, cold spots were found in all cases directly behind each material feature with a medial fill‐in of dose occurring distally. Qualitative agreement of spot perturbance was confirmed between film measurements and MCS. Finally, when comparing integrated depth doses (IDD) by summing over all axial directions, good agreement is observed between TPS and MCS. Conclusions: All dental materials studied substantially perturbed the dosimetry of pristine proton spots both in terms of WET/ S rel as well as the spatial distribution of dose. Proton range was quantifiably shortened, and each dental material affected a cold spot directly behind the object with medial dose back‐filling was observed distally. MCS and Eclipse dose calculations exhibited good agreement with measurements, suggesting that treatment planning without employing avoidance strategies may be possible with further investigation.